How Does Research in Sticky Cost Develop? A Review of Major Themes - Priantana, Riha Dedi; Sayuthi, Sayuthi (Universitas Syiah Kuala, 2020)
Objective This research aims to review the development of sticky cost research up until the last few decades. In general, sticky cost research has developed from one area, the existence of sticky costs, into two areas, namely determinants of sticky costs and the consequences of sticky costs. Design/methodology Literature review was conducted to describe sticky cost research. The sticky costs existence is more intended to ascertain whether sticky costs occur or not, while determinant research is more focused on analyzing the factors that cause sticky costs. The consequence research aims to investigate the impact of sticky costs. This consequence research has touched on research issues in financial accounting, such as earnings predictions, abnormal price predictions.Results Sticky cost research has experienced significant development, not only related to three areas but also the issues of each one, such as cost management accounting, including other studies in the area of corporate strategy and financial issues. Sticky cost research itself is predicted to be one of the interesting research topics in accounting for the next decades.Limitation/Suggestion - This study focuses on sticky cost research in relation with original research of sticky cost, and particularly conducted in developed countries, such as Unites States, English, and Australia. Forthcoming research would also consider any other countries about how sticky research is being progressed hence it may add knowledge of sticky cost research in overall.